2014
DOI: 10.1002/mrm.25312
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in strain rate tensor of the medial gastrocnemius muscle during passive plantarflexion and active isometric contraction using velocity encoded MR imaging: Potential index of lateral force transmission

Abstract: Purpose The strain rate (SR) tensor measures the principal directions and magnitude of the instantaneous deformation; this study aims to track age related changes in the 2D SR tensor in the medial gastrocnemius during passive joint rotation and active isometric contraction. Methods SR tensors were derived from velocity encoded magnetic resonance phase-contrast images in nine young (28 yrs) and eight senior (78 yrs) women. Strain rates along and in the cross-section of the fiber were calculated from the SR te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(98 citation statements)
references
References 26 publications
5
93
0
Order By: Relevance
“…All subjects were included in this study after obtaining informed consent. Six young (26.1 ± 2.3 years, height: 158.6 ± 5.6 cm, mass: 50.8 ± 3.7 kg) and six senior (76.7 ± 8.3 years, height: 153.0 ± 2.0 cm, mass: 57.4 ± 4.3 kg) healthy, moderately active, female subjects were included in this study after informed consent . Two subjects (one young: 25 years, one old: 65 years) were scanned on three separate days to determine the coefficient of variation (CV) and the repeatability coefficients (RC) of the SR components.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All subjects were included in this study after obtaining informed consent. Six young (26.1 ± 2.3 years, height: 158.6 ± 5.6 cm, mass: 50.8 ± 3.7 kg) and six senior (76.7 ± 8.3 years, height: 153.0 ± 2.0 cm, mass: 57.4 ± 4.3 kg) healthy, moderately active, female subjects were included in this study after informed consent . Two subjects (one young: 25 years, one old: 65 years) were scanned on three separate days to determine the coefficient of variation (CV) and the repeatability coefficients (RC) of the SR components.…”
Section: Methodsmentioning
confidence: 99%
“…This provides a number of parameters including SR tensor components in the principal basis, in the muscle fiber basis, and the maximum shear strain. Specifically, the SR tensor provides information on tissue deformation along two orthogonal axes as well as on tissue shear through the off‐diagonal terms of the tensor . These SR components reflect underlying muscle fiber properties like contractility and extracellular matrix material properties like stiffness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it is often assumed that muscles shorten uniformly along their longitudinal axis, whereas evidence has been provided for more complex contraction patterns and it was shown that the direction of shortening is not aligned with the muscle fiber direction . Furthermore, differences in deformation patterns were observed between deep and superficial muscles and between proximal and distal locations . Due to the highly complex pattern in muscle contraction and deformation, 3D visualization of subject‐specific contracting muscles would be extremely valuable.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, diffusion tensor imaging, fractional anisotropy, and T 2 ‐maps were used to investigate muscle quality. On the one hand, diffusion‐weighted imaging and diffusion tensor imaging provide quantitative markers of muscle microstructure, with an increased value of fractional anisotropy as a result asymmetric diffusion in atrophic skeletal muscles . On the other hand, increased T 2 values may suggest significant changes in fiber architecture …”
Section: Discussionmentioning
confidence: 99%